Coupled Analysis of Transient Aerodynamic Characteristics of the Coach under Crosswind in Different Situations - K. Sun; Z. Gu; J. Liu; L. Zheng; H. Hu; J. Gao (Journal of Applied Fluid Mechanics, 2021)
The purpose of this work is to investigate transient aerodynamic characteristics of the coach under the crosswind in straight-line situations with different uniform speeds and uniform accelerations. The transient aerodynamics caused by different speed changes are analyzed using the real-time interaction between aerodynamic simulation and dynamic simulation. The target model is a simplified coach on a full scale. The SST (Menter) K-Omega Improved Delayed Detached Eddy Simulation and overset mesh technique are used to predict the transient aerodynamic loads. The accuracy of the turbulence model is verified by a wind tunnel experiment of the 1/7th scaled coach model. The present results show that the transient aerodynamic loads have different locations of maximum side force and the holding duration of yaw moment for different constant speeds. The speed becomes larger, and the position where the side force is maximum becomes farther away. The holding duration of the top yaw moment is larger simultaneously. Moreover, proper acceleration for low initial driving speed and crosswind of small influence range could build up stability. High speed driving in gust wind is not suggested for unskilled drivers.